2014
DOI: 10.1016/j.gie.2013.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Can patient and pain characteristics predict manometric sphincter of Oddi dysfunction in patients with clinically suspected sphincter of Oddi dysfunction?

Abstract: Background Biliopancreatic-type postcholecystectomy pain, without significant abnormalities on imaging and laboratory test results, has been categorized as “suspected” sphincter of Oddi dysfunction (SOD) type III. Clinical predictors of “manometric” SOD are important to avoid unnecessary ERCP, but are unknown. Objective To assess which clinical factors are associated with abnormal sphincter of Oddi manometry (SOM). Design Prospective, cross-sectional. Setting Tertiary. Patients A total of 214 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As reported elsewhere, abnormal sphincteric pressures were not influenced by the type of sedation or anesthesia and did not correlate with the patient’s clinical characteristics. 27 …”
Section: Resultsmentioning
confidence: 99%
“…As reported elsewhere, abnormal sphincteric pressures were not influenced by the type of sedation or anesthesia and did not correlate with the patient’s clinical characteristics. 27 …”
Section: Resultsmentioning
confidence: 99%
“…In the initial landmark trial demonstrating efficacy of biliary sphincterotomy, patients with type II disease had a marked difference in response rate when they had abnormal basal sphincter pressures. 41 A second trial confirmed similar clinical success in patients with type II disease with elevated baseline manometric results or abnormal pressures following cholecystokinin provocation. 34 Thus, the concept of manometric-directed endoscopic therapy was conceived.…”
Section: Sphincter Of Oddi Dysfunctionmentioning
confidence: 75%
“…39 Patient demographics, pancreaticobiliary enzyme levels, presence of gallbladder disease, pain patterns, use of narcotics, underlying functional disorders, and psychological comorbidities have not been found to correlate with manometric results. 41 Several other limitations of SOM preclude its universal use on all patients with suspected SOD, including (1) need for center expertise and challenging manometry catheter placement; (2) variation in pressure measurements from different types of catheter equipment, variable sphincter lumen size, probe position, and point in time when a spasm is captured; and (3) undue risk involved in catheter insertion during diagnostic ERCP. Measurement of liver enzymes and biliary dilation may be sufficient, if not superior, to manometry for diagnosis and predicting response to therapy.…”
Section: Elevated Amylase/lipasementioning
confidence: 99%
“…Rome III characterized FPSD pain in upper abdominal location and separated by pain‐free intervals (Table 1) (8). Many adults with manometry‐defined FPSD, however, experience more frequent or daily abdominal pain (17). Whether this pain pattern is applicable to children is unknown given that young children are less capable of articulating pain characteristics.…”
Section: Classification Of Functional Pancreatic Sphincter Dysfunctionmentioning
confidence: 99%